2019
DOI: 10.37940/ajvs.2019.12.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of arginine and selenium with vitamin E in some biochemical properties of Inseminated ewes

Abstract: The study was conducted in one of the fields of the private sector within Basaaer the village of the district of Hit / Anbar at 180 km west of Baghdad, during the period from 17/4/2018 to 30/5/2018. 28 ewes with an age of 2-4 years with a weight of 40-50 kg with at least one birth. All ewes were tested using ultrasonography to ensure that they were free of pregnancy before the start of the experiment. Synchronization of estrus with intravaginal sponges was achieved in ewes, and inseminated with rams at the end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
0
1
Order By: Relevance
“…In the current study this result had disagreed with [13] observed that treated ram with 0.03 g/kg/bw Se yeast had not a significant increase between treatment and control groups. The results of the current study had disagreement with [29], who found, the adding selenium with vitamin E at 2 ml/animal, showed non-significant differences between treated and control groups. The main advantage of high Se consumption is that it can prevent liver damage in certain situations.…”
Section: Total Protein (Tp)contrasting
confidence: 99%
“…In the current study this result had disagreed with [13] observed that treated ram with 0.03 g/kg/bw Se yeast had not a significant increase between treatment and control groups. The results of the current study had disagreement with [29], who found, the adding selenium with vitamin E at 2 ml/animal, showed non-significant differences between treated and control groups. The main advantage of high Se consumption is that it can prevent liver damage in certain situations.…”
Section: Total Protein (Tp)contrasting
confidence: 99%